2022
DOI: 10.3390/v15010037
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Temporal Variability of Hepatitis E Virus Circulation in the Russian Federation

Abstract: The factors influencing hepatitis E virus (HEV) circulation remain largely unexplored. We investigated HEV seroprevalence in humans and the prevalence of infection in farm pigs and rabbits in different regions of the Russian Federation, as well as the genetic diversity and population dynamics of the HEV. The anti-HEV IgG antibody detection rates in the general population increase significantly with age, from 1.5% in children and adolescents under 20 years old to 4.8% in adults aged between 20 and 59 years old … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…In this study, we investigated the proportion of blood donors with viremic HEV infection to assess whether HEV RNA testing should be implemented for blood services in Russia. Previous studies have shown that the HEV epidemiology in Russia is similar to that observed in many industrialized countries which are of intermediate HEV endemicity, with rather high seroprevalence due to asymptomatic infections in the general population and increased seroprevalence rates in seniors, and zoonotic HEV-3 is the causative agent of autochthonous cases [ 14 ]. Thus, although TT-HEV cases have not been reported in Russia so far, they are expected to exist but are unrecognized and/or undiagnosed.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In this study, we investigated the proportion of blood donors with viremic HEV infection to assess whether HEV RNA testing should be implemented for blood services in Russia. Previous studies have shown that the HEV epidemiology in Russia is similar to that observed in many industrialized countries which are of intermediate HEV endemicity, with rather high seroprevalence due to asymptomatic infections in the general population and increased seroprevalence rates in seniors, and zoonotic HEV-3 is the causative agent of autochthonous cases [ 14 ]. Thus, although TT-HEV cases have not been reported in Russia so far, they are expected to exist but are unrecognized and/or undiagnosed.…”
Section: Discussionmentioning
confidence: 81%
“…Two particular regions, Moscow and Belgorod, were chosen for this study, because the average anti-HEV IgG prevalence rate in the general population in the former is the same as the country’s average (4%), but it is four times higher in the latter, reaching 16.4% [ 14 ], which is indicative of a higher intensity of virus circulation. Indeed, the ratio of HEV RNA positivity among blood donors appeared to be 1.5 times higher in Belgorod than in Moscow (1:2936 and 1:4844, respectively), although this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations